Deconstructing The Position Of The Savior And The Damned In Flannery O'connor's “The Lame Shall Enter First” - Sumaryani, Sri (English Education Department, Universitas Islam Indonesia, 2013)
This paper aims to show the use of deconstruction theory by Jacques Derrida to offer other possible meanings in a short story entitled “The Lame Shall Enter First” by Flannery O'Connor. The researcher shows the flaw in the binary oppositions constructed by the text and reveals the failure of the logical arguments of the oppositions by redefining qualities of the opposite characters in the story, Sheppard, Norton, and Rufus. The researcher used descriptive-qualitative method as it is a qualitative research of which the data are nonnumeric. The researcher finds three binary oppositions that become the center of the story. The first pair of binary opposition is religion and logic. The second are selfishness and compassion, and the third is ignorance and sympathy. The oppositions are represented by characters Sheppard, Rufus, and Norton. By closely reading the text and attacking the basic premises of the text, the researcher finds that the binary oppositions no longer serve as the foundation of the story since the story proves that all those binary oppositions eventually show otherwise.Keywords: deconstruction, binary opposition, character